PELATIHAN DAN PENDAMPINGAN PENGELOLAAN BUMDES BERKELANJUTAN UNTUK AKSELERASI BUMDES MANDIRI - Muhammad Faisal Riza; Irfan Kharisma Putra; Dewi Noor Fatikhah Rokhimakhumullah; Fiaz Muthia Firlianna (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
the community service program is packaged in the form of a Sustainable BUMDes Training and Assistance package for the Acceleration of Independent BUMDes. The training and mentoring are carried out starting from the business management aspect of BUMDes, Human Resources (HR) management which of course acts as the direct manager of BUMDes, and financial aspects including taxation. The purpose of this activity is to help improve the governance of BUMDes, together with the village government, the community, and the private sector; through training and mentoring efforts to explore the natural potential and the potential of human resources owned. The method used is divided into three stages, namely 1) analyzing the mapping of the problems faced by BUMDes in Ampeldento Village, 2) conducting socialization about the steps for establishing BUMDes in accordance with regulations, 3) providing training and assistance in business development through exploring potential resources. owned village people and trained in making simple financial reports. The service program carried out has had a good impact on the development of BUMDes and related human resources so that BUMDes is expected to be sustainable so that it can provide benefits to the community in a sustainable manner.